Recent developments of planar printed circuit board (pcb) transformer technology - Hui,RSY (Hkie Transactions Hong Kong Institution of Engineers, 2003)
Rapid developments of planar magnetics in recent years have prompted new applications of planar transformers in electronic industry. The low-profi’e features of planar magentics make them attractive in many electronic systems that have stringent thickness requirements. In this article, some recent progress of planar PCB transformers and their applications are described. Comparisons of canventional and pianar transformers are reviewed. New trend of integrated electronic packaging in power electronic systems is briefly discussed. © 2003 Taylor & Francis Group, LLC.